Methodology for Determining the Effective Parameters of Concrete-Filled Steel Tube Beam Trusses with Top-Deck Traffic - Spivak, D. S.; Kliuchnyk, S. V. (Science and Transport Progress, 2025)
Purpose. This article presents a methodology for determining the effective dimensions of main beam trusses with triangular lattices and top-deck traffic arrangement using concrete-filled steel tubes. The aim of the study is to develop an algorithm that enables identification of optimal geometric and structural parameters of such trusses based on comprehensive consideration of material properties, loads, and structural element behavior. Methodology. The research is based on numerical modeling using Mathcad and LIRA–CAD software packages. Within its framework, a uniform search method is implemented, which ensures the generation of all possible combinations of truss parameters, their analysis, and filtering according to efficiency criteria. Special emphasis is placed on the upper chord of the trusses, made of concrete-filled steel tubes, which allows for maximum utilization of the load-bearing capacity of these elements. The calculations incorporate standard Ukrainian loads (AK, NK, CK), and verification of the operating conditions of concrete-filled steel tube elements is performed in accordance with Eurocode 4 provisions. Results. The developed algorithm facilitates automatic generation, verification, and filtering of variants considering load-bearing capacity limits. The validation of calculation results confirmed their compliance with regulatory requirements and effective material use. The average computation time per variant is sufficient for determining efficient concrete-filled steel tube cross-sections but is not a limiting factor and indicates potential for further optimization and acceleration of the algorithm. Originality. The authors propose a methodology for searching optimal parameters of segmented concrete-filled steel tube beam trusses with triangular lattices and top-deck traffic layout. For the first time, a detailed multi-level calculation structure of concrete-filled steel tube trusses under regulatory loads according to Ukrainian codes (DBN) is introduced, with element design carried out in accordance with Eurocodes. Practical value. The study develops an adaptive tool aimed at optimizing concrete-filled steel tube truss structures in bridge engineering. The proposed approach contributes to reducing material consumption and ensures rational use of concrete-filled steel tubes in the elements of main beam trusses.